Value Chain digitalization and technological development as innovation catalysts in small and medium-sized enterprises - Raquel Marín; Francisco Javier Santos Arteaga; Madjid Tavana; Debora Di Caprio (Journal of Innovation & Knowledge (JIK), 2023)
We analyze the effects of digitalization and the knowledge acquired through vertical and institutional cooperation across the value chain on the introduction of patents and technological, namely, product and process, innovations in large, and small and medium-sized enterprises (SMEs). We study the case of Spain as a digitally competitive economy displaying a relatively low innovation score, a feature reversing the trend observed in most European Union countries. Three empirical scenarios, one for each innovation output, are defined and analyzed following a random-effects probit panel model separately estimated for large firms and SMEs. The sample used in the empirical analysis comprises 1,369 manufacturing firms, out of which 508 are large and 862 SMEs. The empirical results confirmed the importance of digitalization and collaboration across the value chain for all firms, regardless of size. We also observe that the performance of internal R&D activities fosters the introduction of patents and technological innovations across all firms. The main theoretical implications of the empirical results are discussed, and different policy recommendations suggested.
Keywords: O32; O31; O14; 650; Digitalization; patents; Product and process innovations; Digital value chains; Research and development; Small and medium-sized enterprises